2013
DOI: 10.1182/blood-2013-02-483156
|View full text |Cite
|
Sign up to set email alerts
|

Rasip1 regulates vertebrate vascular endothelial junction stability through Epac1-Rap1 signaling

Abstract: • RASIP1 is required for stabilizing nascent patent blood vessels in both mice and zebrafish.• RASIP1 is a dynamic effector of EPAC1-RAP1 signaling that controls actin bundling and restricts junction remodeling in vitro and in vivo.Establishment and stabilization of endothelial tubes with patent lumens is vital during vertebrate development. Ras-interacting protein 1 (RASIP1) has been described as an essential regulator of de novo lumenogenesis through modulation of endothelial cell (EC) adhesion to the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 53 publications
9
100
0
Order By: Relevance
“…Here, we show that active Rap1 achieves this by inducing the translocation of all three components-Radil, Rasip1, and ArhGAP29 -to the plasma mem- brane. Our results confirm that the previously reported Rap1-dependent plasma membrane localization of Radil (24) and Rasip1 (18) are due to direct binding of the effectors to active Rap1 through their RA domains. Whereas the translocation of Arh-GAP29 depends on Radil alone, a trimeric complex between Radil, Rasip1, and ArhGAP29 is formed upon Rap1 activation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Here, we show that active Rap1 achieves this by inducing the translocation of all three components-Radil, Rasip1, and ArhGAP29 -to the plasma mem- brane. Our results confirm that the previously reported Rap1-dependent plasma membrane localization of Radil (24) and Rasip1 (18) are due to direct binding of the effectors to active Rap1 through their RA domains. Whereas the translocation of Arh-GAP29 depends on Radil alone, a trimeric complex between Radil, Rasip1, and ArhGAP29 is formed upon Rap1 activation.…”
Section: Discussionsupporting
confidence: 81%
“…Presumably, Rasip1 controls the activity of ArhGAP29. Indeed, it was demonstrated that depletion of Rasip1 results in increased Rho-GTP levels in three-dimensional HUVEC cultures (18). However, this was not observed in two-dimensional HUVEC cultures (11,18,20), implying that Rasip1 could also function independently of ArhGAP29 in the control of endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…82 EPAC1-Rap1 pathway has also been reported to downregulate RhoA activity through a multimeric protein complex containing the Rap1 effectors, Radil and Rasip1 and the Rho GTPase-activating protein 29 (ArhGAP29), leading to decreased cell contractility and stabilization of VE-cadherin-induced cell-cell adhesion ( Figure 5). [87][88][89] In addition, the Rap1-binding protein K-Rev1 Interaction Trapped gene 1 (KRIT1) was shown to be involved in EPAC1/Rap1-induced permeability of endothelial cell-cell junctions. 90 Although EPAC1 activates Rap1, not all EPAC1 effects on vascular EB function can be attributed to the activation of Rap1.…”
mentioning
confidence: 99%
“…Knockdown of either isoform leads to disruption of integrin-mediated adhesion, with consequences such as [47][48][49][50] Further, loss-of-function studies of RAP1 in vitro result in VE-cadherin disorganization, a reduction in linear junction-associated actin, and an increase in FAJs ( Table 1). [51][52][53][54] There are discrepancies in the literature as to whether RAP1A or RAP1B is the primary contributor to the formation and stabilization of endothelial junctions, as RNAi-mediated knockdown of either isoform leads to disruptions of VE-cadherin staining, increased formation of FAJs and/or gaps between cells, and reduction in transendothelial resistance ( Table 1). 54 These inconsistencies may be a result of utilization of endothelial cells from different vascular beds, different siRNA sequences with possible off-target effects, or different culture conditions.…”
Section: Rap1 As a Central Mediator Of Endothelial Cell-cell And Cellmentioning
confidence: 99%
“…67 Subsequent work demonstrated that Rasip1 is highly expressed in embryonic and adult vasculature and is below detectable levels in non-vascular tissue in vertebrates. 53,68,69 We and others have shown that knockout of Rasip1 in mice results in pericardial edema, multifocal hemorrhage, and midgestational embryonic lethality, resulting from malformation of vasculogenic blood vessels and disruption of circulation (Table 1). 53,69 In addition, morpholino-mediated knockdown of rasip1 expression in the developing zebrafish embryo causes blood vessel defects, including irregularly shaped axial vessels and hemorrhage around cranial and intersomitic vessels.…”
Section: A Role For the Rap1 Effector Rasip1 In Junctional Actin Assementioning
confidence: 99%